Deciphering the Inheritance Mechanisms of Fruit Color in Tomato - Kumar, Sandeep; Sharma, Aditi; Thakur, Bhupinder S.; Mehta, Devinder K.; Kansal, Sandeep; Dogra, R. K. (International Journal of Economic Plants, 2025)
The experiment was conducted during kharif, 2020–21 at Regional Horticultural Research and Training Station, Bajaura, Kullu, Himachal Pradesh (175 121) a breeding program was initiated using two distinct tomato genotypes: Solan lalima and BN-7 to explore the development of novel colour development. These parent varieties were strategically chosen for their complementary traits, with the goal of combining and enhancing desirable characteristics, including unique color expressions, in their progeny. The initial step involved crossbreeding these genotypes to produce F1 hybrid plants. Following this hybridization, we embarked on a process of repeated self-pollination (selfing) and backcrossing. This technique, employed over six successive generations, allowed us to carefully select and propagate plants exhibiting the most promising combinations of traits, particularly focusing on fruit color. Chi-square analysis further revealed that Solan Lalima (red)×BN-7 (yellow) showed dominance of red colour over yellow colour.